Teaching Foreign Languages Using Modern Methods and Educational Technologies to Foster the Development of Critical Thinking - Allamuratova K H. (Miasto Przyszłości, 2023)
The article describes the use of technology for developing critical thinking in English lessons. It provides examples of how to apply techniques of this technology. The article presents the positive aspects of this technology as well as the difficulties in using it for developing critical thinking.